Correlation Epidermal Growth Factor Receptor Mutation with Non-small Cell Lung Cancer in Passive Smokers: A Review - Prameswari, Yuda Nabella; Dwi Anita Suryandari (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2022)
Epidermal growth factor receptor (EGFR) is a transmembrane glycoprotein with an extracellular epidermal growth factor binding domain and an intracellular tyrosine kinase domain through signaling pathways to regulate cellular proliferation. Epidermal growth factor receptor binding to its ligand will result in autophosphorylation by intrinsic tyrosine kinase activity, thereby triggering multiple signal transduction cascades. Constant or sustained activation of these downstream target sequences is thought to result in a more aggressive tumor phenotype. Mutations in EGFR are associated with non-small cell lung cancer in passive smokers.